Siradge ad-Din as-Sakkaki and His Work “Miphtakh al-Ulum” (Journal of Oriental Studies, 2019)
Yusuf ibn Abi Bakr ibn Mukhammad abn Ali Yakub asSakkaki alKharezmi Siradge addin (555 / 1160627 / 1230) is a distinguished scientist of Arabic, semantics, literature, prosody and poetry. The article discusses life and creative work of asSakkaki in the field of Arabic rhetoric, its formation and the development. His famous work “Miphtakh alUlum”, in particular, its third part was written in compliance with the most necessary achievements of previous scientists in this field, thus concentrating the scattered fundamental principles in one work up to now. The considered thesis is distinguished by the convenient division into the chapters and the correct distribution of topics. The work includes the issues of phonetics, the three sections on word formation, the grammar, and also the sections of rhetoric. The subsequent chapters discuss the prosody and dialectics problems, completing the work with a chapter on poetical rhymes. All the considered issues in the work are particular importance for the Arabicresearchers, fascinated by the creative work and art criticism.   The value of this work by asSakkaki also lies in the successful concentration of the Arabic linguistics principles in one work. It provides the opportunity for the deeper comprehension of the Arabic, the complete understanding of the Quran, and gives the key to the explanation of the Sharia knowledge secrets. Key words: Arabic, «alMiphtakh», rhetoric, stylistics, chromatic accordion, grammar, morphology, rule, work, imam, scientist.